Diagenetic Processes in Aquaculture Ponds Showing Metal Accumulation on Shrimp Gills - Lemonnier, Hugues; Royer, Florence; Caradec, Florian; Lopez, Etienne; Hubert, Clarisse; Rabiller, Émilie; Desclaux, Térence; Fernandez, Jean-Michel; Andrieux-Loyer, Françoise (Frontiers in Marine Science, 2021)
The gill is the organ by which many toxic metals are taken up by crustaceans. Iron is known to precipitate at its surface, a phenomenon recently observed in some tropical aquaculture ponds. The present study uses a field approach to understand better the environmental conditions and ecological processes involved in this deposit. Because shrimp are exposed to reduced products originating from organic waste accumulated in the sediment, spatial variation in pH, redox potential and concentrations of dissolved metals in pore water were investigated in these ponds. Total organic carbon, acid volatile sulfide and pyrite were also analyzed in the solid phase. Fe2+ in pore waters showed high spatial variability between ponds and within the same pond with concentrations up to 1193 µmol.l-1. Behaviors of Fe2+, Mn2+ and Co2+ in pore water were similar. Four geochemical environments were identified, based on their physico-chemical characteristics. Highest concentrations for Fe2+, Mn2+ and Co2+ in sediment pore water occurred in slightly acidic and suboxic conditions. When the sediment became anoxic, the H2S produced reacted with Fe2+ and/or Co2+ to form acid volatile sulfide and pyrite. When pH increased, the concentration of free H2S rose up to 736 µmol.l-1. With neutral and suboxic conditions, dissolved metal concentrations could be controlled by their precipitation as oxides and hydroxides. The production of pyrite suggested the existence of a possible process of sediment acidification between two crop periods through the production of sulfuric acid. This acidification could increase with pond age and be the cause of the accumulation of reduced metal after 30 years of aquaculture activity.